Monitoramento e diagnóstico da qualidade da água do Ribeirão Morangueiro - Hespanhol, Katia Maria Hipolito (2009)
The city of Maringá was carefully planed, however its water resources have been degraded in the last decades due to the urbanization process. The stream under study has its spring in the urban area of Maringá, receives the effluent of a sewage treatment plant and flows into stream Sarandi that flows into Pirapó river, near the captation of water that supplies the city.This study aims to monitor and diagnose the water quality of the stream Morangueiro, comparing its parameters with the ones established by CONAMA resolution number 357/2005.The work methodology consisted of field collections along the stream, being conducted physical, chemical and biological analyses of the water samples collected. Results showed that the stream Morangueiro water has high concentrations of organic loadings, nutrients and coliforms, once the human activities, through the launch of domestic sewage is the mainsource of pollution, and the launch of effluent of the sewage treatment plant is the most significant. So, its water do not conformidade established to class 2 by resolution number 357/2005 of CONAMA.